The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000093256
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Shakuyaku-kanzo-to on Muscle Cramp in Hemodialysis Patients

Abstract: We administered 2.5 g of Shakuyaku-kanzo-to granule to 61 patients who had muscle cramp during hemodialysis (HD) sessions and examined its immediate effects. We selected 10 patients who wanted to take the drug at home, out of cases, for whom the drug was effective on the study described above and had them take the drug in the same way at the beginning of muscle cramp at home examined the effects. In the study during HD sessions, muscle cramp and its associated pain disappeared in 5.3 ± 3.9 min on average in 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…We found that the inhibitory effect of intraduodenally administered SKT and G. radix occurred within 15 min of administration, which is consistent with the reported onset of the clinical effect of SKT following oral administration (Hyodo et al, 2006). Further, six of the eight G. radix isolates (liquiritin apioside, liquiritigenin, isoliquiritin apioside, isoliquitirigenin, flavonoids; glycyrrhetinic acid, a triterpenoid; glycycoumarin, a coumarin derivative) followed a similar time course of inhibition as SKT and G. radix, suggesting that these were indeed the primary constituents of SKT with an antispasmodic effect.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the inhibitory effect of intraduodenally administered SKT and G. radix occurred within 15 min of administration, which is consistent with the reported onset of the clinical effect of SKT following oral administration (Hyodo et al, 2006). Further, six of the eight G. radix isolates (liquiritin apioside, liquiritigenin, isoliquiritin apioside, isoliquitirigenin, flavonoids; glycyrrhetinic acid, a triterpenoid; glycycoumarin, a coumarin derivative) followed a similar time course of inhibition as SKT and G. radix, suggesting that these were indeed the primary constituents of SKT with an antispasmodic effect.…”
Section: Discussionsupporting
confidence: 89%
“…Some of the precipitating factors include strenuous exercise, metabolic disorders, electrolyte disturbance, pregnancy, and iatrogenic causes such statins, diuretics, and immunosuppressants (Miller and Layzer, 2005). In Japan pharmacotherapy for muscle cramps includes muscle relaxants, anticonvulsants, vitamin and mineral supplements, and traditional Japanese herbal medicines (Kampo) such as shakuyakukanzoto (SKT) (Hinoshita et al, 2003;Hyodo et al, 2006). Most muscle relaxants and anticonvulsants, however, have untoward adverse effects of hepatotoxicity and central nervous system (CNS) depression, and those that directly target the skeletal muscles while sparing the CNS are scare (Richards et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, several kinds of Kampo formula have been widely used for palliative care including cancer associated symptoms and adverse effect of chemotherapy in Japan 5) . SKT, a Kampo formulation with anticholinergic and prostaglandin inhibitory effect has been reported to be effective in reducing muscle pain, muscle spasms, joint pain and numbness 2,[6][7][8] . So, we first tried SKT for the treatment for the muscle cramps induced by S-1 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence was reported only 0.2% in the treatment with S-1 1) . For the measure of this adverse event, it is reported that Shakuyaku-kanzo-to (SKT) a Kampo medicine could be effective 2) . In this report, we show the experience of the patient who was effective by the administration of Goshajinkigan (GJG) a different Kampo medicine to improve the muscle cramp arose by using S-1 for the treatment of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle cramp frequently develops under abnormal serum K + concentrations 4,11) during exerciseinduced dehydration 12) and hemodialysis 3,4) . These indicate the possible involvement of intra -and extracellular K + concentration charge in muscle cramps.…”
Section: Introductionmentioning
confidence: 99%